Enhancing Security And Privacy For E-Commerce Database - et. al., kanakanti balakrishna reddy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The cloud computing are the services offered in the Internet and everyone using the cloud services and more over every android user using the database. All users are having some confidential information. Proposed system provides security for the information in databases by implementing the one of the best algorithms and these algorithms may provide more security. Unauthorized people may access confidential information without any permission. The popular security algorithms are AES (Advanced encryption standard), DES (Data encryption standard, CES (cipher block standard ,3DES, RSA. These algorithms we have encrypt the data and decrypt them to protect from the attack or any Phishing attacks or any vulnerability to keep our information safe. But the attackers can break present technologies and access the information. In this kind of scenario, at least sensitive private information should not be disclosed. Hence the proposed system concentrates on the privacy of an information and considers the biometric security.